Association between Cervical Spine Degeneration and the Presence of Dens Fractures - Betsch, Marcel; Blizzard, Sabina; Krishnamoorthy, Bala; Yoo, Jung (Zeitschrift für Orthopädie und Unfallchirurgie, 2020)
Purpose Results of a small case series indicate an increased risk of dens fractures in patients with osteoarthritis. The purpose of this retrospective cohort study was to analyze the relative risks associated with degeneration of the cervical spine in the occurrence of dens fractures in older patients.Methods We performed a retrospective CT study of 1,794 patients > 55 years of age with and without dens fractures for signs of osteoarthritis (OA).Results OA of the atlanto-dens interval (AdI) was present in 75.9% of fracture patients, whereas 63.5% of non-fracture patients had OA of the AdI (p = 0.04). In cases of osteoarthritis of the facet joints, we did find a significant increase (p < 0.05) in the dens fracture risk in patients with OA.Conclusions This study indicates an association between OA of the cervical spine and the risk of sustaining a dens fracture. OA can lead to a reduction in the range of motion of the cervical spine. As a consequence, a relatively low-energy trauma can induce a forced sagittal motion, which will produce a torque at the base of the odontoid process resulting in a fracture.
Keywords: osteoarthritis; cervical spine degeneration; dens fractures; odontoid process